The Characteristics of the Essay by some Contemporary Slovenian Female Essayists - Vollmaier Lubej, Janja (Slavia Centralis, 2023)
The present paper reflects on the literary work of selected contemporary Slovenian female essayists, with special focus on their thematic and stylistic characteristics. It should be noted that not much research has been done focusing on the literary work of contemporary Slovenian female writers, although they have written and still write across a variety of genres. The theoretical part of the article presents the findings and studies of Denis Poniž, Janko Kos and Miran Štuhec, with respective references, especially the historical context of the European and Slovenian essay and essayistic narrative prose. The paper then focuses on the essays of Slovenian female authors from 1993 to the present, also highlighting reflections on selected German, Polish, Russian and American female essayists. This is followed by an overview of the essays by selected authors, namely the essay collections Slovenija, moja Afrika (1993) by Silvia Borovnik, Tek na mestu (2017) by Renata Salecl, Vseživo (2017) by Urša Zabukovec and Naredite Ameriko spet oblavladljivo (2018) by Katja Perat, which highlights essayist thought as well as thematic and stylistic similarities and differences.
Keywords: contemporary Slovenian female essayists, Slovenian essay, female authorship, Silvija Borovnik, Renata Salecl, Urša Zabukovec, Katja Perat